Transformation of Saccharomyces cerevisiae by pET plasmid using lithium acetate (World Journal of Experimental Biosciences, 2015)
The recombinant pET 16b was propagated and amplified in E. coli using heat shock method, then plated and incubated on luria agar containing ampicillin (100μg/ml) for 18 hours at 37ºC. One colony was picked and mini-culture was made. Transformed E. coli was cultured on luria broth containing ampicillin. After incubation 18 h at 37˚C the recombinant plasmid was extracted using QIAprep Spin Miniprep Kit from transformed E. coli and transferred to Saccharomyces cerevisiae using lithium acetate/SS carrier DNA/PEG. The positive transformed clones were grown on selective media lacking of tryptophan. The plasmid was extracted using the same extraction kit with some modification and the concentration of obtained DNA was 70.8 ng/μl measured by Nanodrop. In this study, the recombinant pET 16b that amplified in E. coli was transformed in S. cerevisiae by lithium acetate method.